Penyuluhan Perkawinan di Bawah Umur dan Dampaknya terhadap Remaja di Desa Pappandangan Polewali Mandar - Muhammad Adam HR; Novia Sandra Dewi; Septian Harianto; Nur Aisyah; Annisa Ramadhani K (LP3M IAIFA Kediri, 2026)
Underage marriage remains a significant social issue in rural Indonesia, particularly in Pappandangan Village, Polewali Mandar, conflicting with national laws setting the minimum marriage age at 19 years and hindering adolescent physical, psychological, and social development. This community service focuses on educating youth about the risks and impacts of early marriage on education, reproductive health, mental well-being, and family sustainability. The primary objective is to enhance adolescents' and community's awareness of early marriage dangers, promote delayed marriage for maturity in education, mental, and economic aspects, and foster preventive attitudes aligned with national and Islamic law principles. The approach employs Participatory Action Research (PAR) through direct face-to-face counseling, interactive discussions, Q&A sessions, and contextual integration of socio-cultural and religious values, positioning youth as active participants. Results show significant improvements in participants' knowledge pre- and post-intervention, with increased critical awareness of early marriage risks, identification of multidimensional factors (economic, social, cultural, religious), and shifts toward positive attitudes prioritizing education and self-preparedness, laying foundations for reduced early marriage practices.